2015
DOI: 10.4103/0970-4388.148976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral health status of Santal (Tribal) children of West Bengal

Abstract: The study showed there was no significant difference (P > 0.05) between the average decayed extracted filled teeth (deft)/DMFT for boys and girls in deciduous and permanent dentition. But in mixed dentition this value for the boys was significantly higher (P < 0.001) than girls. 'Z' values were found to be non significant when compared mild, moderate and severe gingivitis between boys and girls in each dentition group, but mild gingivitis significantly increases from deciduous dentition to mixed to permanent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The present study evidently showed that a majority (74.2%) of Santhali tribals routinely used twigs of sakhua trees ( Shorearobusta ) to clean their mouth. The results of the present study are in agreement with the studies conducted by Mandal et al .,[ 7 ] Vaish et al .,[ 11 ] Bhowate et al .,[ 12 ] Varenne et al .,[ 13 ] Abdul-Kadir Yassin,[ 14 ] Vaish,[ 15 ] and John et al . [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study evidently showed that a majority (74.2%) of Santhali tribals routinely used twigs of sakhua trees ( Shorearobusta ) to clean their mouth. The results of the present study are in agreement with the studies conducted by Mandal et al .,[ 7 ] Vaish et al .,[ 11 ] Bhowate et al .,[ 12 ] Varenne et al .,[ 13 ] Abdul-Kadir Yassin,[ 14 ] Vaish,[ 15 ] and John et al . [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted across the world on the tribal populace, and in reference to oral health, to name a few, the Paniya tribes of Wayanad[ 5 ] and Kalpetta,[ 6 ] Kerala, the Santal tribals of West Bengal,[ 7 ] the tribals of the Eastern Ghats,[ 8 ] the Orao tribals in Rangpur District, Bangladesh,[ 9 ] and the Xukuru ethnic group of Pesqueira, Brazil. [ 10 ] The Santhals are predominant in Jharkhand State in Santhal Paragana, Singhbhum, Dhanbad, Hazaribagh, Giridih, and Ranchi Districts.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches were done among the tribal population in India and the studies showed that the oral health status and oral hygiene practices were very poor among the tribal population from different states of India. [ 19 24 25 26 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with a study conducted by Mandal et al . [ 5 ] where the highest prevalence of dental caries was seen during mixed dentition. The caries prevalence in this study increased with age, which is in accordance with a study conducted by Adhikari et al .…”
Section: Discussionmentioning
confidence: 99%